Nontrivial Solutions for a System of Second-Order Discrete Boundary Value Problems. (24th August 2020) - Su, Hua; Wang, Yongqing; Xu, Jiafa
Abstract : In this work, we shall study the existence of nontrivial solutions for a system of second-order discrete boundary value problems. Under some conditions concerning the eigenvalues of relevant linear operator, we use the topological degree theory to obtain our main results.